Strategi Pengelolaan Air Terjun Madakaripura Kabupaten Probolinggo Jawa Timur - Hasnia Minanda; I Nyoman Sunarta; I Nyoman Sukma Arida (JURNAL MASTER PARIWISATA, 2022)
Madakaripura Waterfall as the highest waterfall in Java Island has shown an increase number of tourists visit every year, however there are still many problems such as lack of facilities, accessibility and quality of human resources. This problem makes research on management strategy at Madakaripura Waterfall important to do. The research aimed to identify the existing conditions of tourist attraction, then the motivates and obstacles for the management and management strategy that will be carried out by stakeholders. This research used qualitative descriptive analysis and SWOT analysis techniques. Data collection was done by observation, interviews, documentation and literature studies. The results showed that the position of Madakaripura Waterfall based on Tourism Area Life Cycle theory is in involvement stage. The motivation behind the management are strengths and opportunities and the obstacle for management are weaknesses and threats. The management strategies by stakeholders are planning, organization, actuating and controlling. From the management strategy by stakeholders, this study offers a new management strategy for consideration and suggestions by the SO, WO, ST, and WT strategy which are compiled as follows: dig and use the potential of Madakaripura Waterfall, designing attractive and affordable tour packages to welcome tourists in the new normal era, the necessity of authority agency to synergize both managers, create strict penalty for local people, improving the quality of human resources, improving mitigation and pay attention to the quality of service for tourists. Keywords: madakaripura waterfall, natural tourist attraction, management strategy.